Probing oxygen activation on plasmonic photocatalysts - Dingenen, Fons; Borah, Rituraj; Ninakanti, Rajeshreddy; Verbruggen, Sammy W. (Frontiers in Chemistry, 2022)
In this work we present an assay to probe the oxygen activation rate on plasmonic nanoparticles under visible light. Using a superoxide-specific XTT molecular probe, the oxygen activation rate on bimetallic gold-silver ‘rainbow’ nanoparticles with a broadband visible light (> 420 nm) response, is determined at different light intensities by measuring its conversion into the colored XTT-formazan derivate. A kinetic model is applied to enable a quantitative estimation of the rate constant, and is shown to match almost perfectly with the experimental data. Next, the broadband visible light driven oxygen activation capacity of this plasmonic rainbow system, supported on nano-sized SiO2, is demonstrated towards the oxidation of aniline to azobenzene in DMSO. To conclude, a brief theoretical discussion is devoted to the possible mechanisms behind such plasmon-driven reactions.